Prevalence of attention deficit/hyperactivity disorder (ADHD) in congenital heart diseases (CHD), a systematic review and meta-analysis. (3rd October 2022) - Tarek Hasan, M; Shaban Abdelgalil, M; A Elbadawy, M; Mahmoud Elrosasy, A; Elkhadragy, A; K Awad, A
Abstract: Introduction: Neuropsychiatric disorders are well-established in patients with congenital heart defects (CHD); moreover, patients with CHD have higher three to four times risk for inattention and hyperactivity. Several published studies have investigated the prevalence of attention deficit/hyperactivity disorder (ADHD) among patients with CHD, thus we conducted our meta-analysis in an attempt to further investigate the role of CHD in increasing the incidence of ADHD. Methods: Electronic databases were systematically searched to identify any observational or interventional studies that compared the effects of congenital heart disease on the incidence or progression of ADHD. Pooled mean difference (MD) and their 95% confidence intervals (CI) were calculated using inverse variance and fixed effect models Results: We identified eight studies with 120187 patients with a mean age of 15.8 years. Patients with CHD compared to healthy population have statistically significant higher scores in ADHD inattention subscale, ADHD hyperactivity-impulsivity subscale, ADHD combined scale (Fig. 1) with MD of 0.25 [95% CI 0.13, 0.37, p<0.0001], 0.16 [95% CI 0.04, 0.28, p=0.008], 0.23 [95% CI 0.11, 0.35, p=0.0002], respectively. Furthermore, ADHD index T score (Fig. 2) for both self-reported and informant report showed a statistically significant increase in CHD with MD of 0.42 [95% CI 0.26, 0.58, p<0.00001] and 0.86 [95% CI 0.52, 1.19, p<0.00001]. Conclusion: CHD showed an associated increased risk for the development of ADHD which was confirmed with several ADHD scales. Funding Acknowledgement: Type of funding sources: None.